P2Y receptor-mediated transient relaxation of rat longitudinal ileum preparations involves phospholipase C activation, intracellular Ca2+ release and SK channel activation - Mader Felix; Krause Ludwig; Tokay Tursonjan; Hakenberg Oliver W; Köhling Rüdiger; Kirschstein Timo (Acta Pharmacologica Sinica; Vol 37, No 5 (May 2016): Acta Pharmacologica Sinica, 2017)
Aim: Purinergic signaling plays a major role in the enteric nervous system, where it governs gut motility through a number of P2X and P2Y receptors. The aim of this study was to investigate the P2Y receptor-mediated motility in rat longitudinal ileum preparations. Methods: Ileum smooth muscle strips were prepared from rats, and fixed in an organ bath. Isometric contraction and relaxation responses of the muscle strips were measured with force transducers. Drugs were applied by adding of stock solutions to the organ bath to yield the individual final concentrations. Results: Application of the non-hydrolyzable P2 receptor agonists α,β-Me-ATP or 2-Me-S-ADP (10, 100 μmol/L) dose-dependently elicited a transient relaxation response followed by a sustained contraction. The relaxation response was largely blocked by SK channel blockers apamin (500 nmol/L) and UCL1684 (10 μmol/L), PLC inhibitor U73122 (100 μmol/L), IP3 receptor blocker 2-APB (100 μmol/L) or sarcoendoplasmic Ca2+ ATPase inhibitor thapsigargin (1 μmol/L), but not affected by atropine, NO synthase blocker L-NAME or tetrodotoxin. Furthermore, α,β-Me-ATP-induced relaxation was suppressed by P2Y1 receptor antagonist MRS2179 (50 μmol/L) or P2Y13 receptor antagonist MRS2211 (100 μmol/L), and was abolished by co-application of the two antagonists, whereas 2-Me-S-ADP-induced relaxation was abolished by P2Y6 receptor antagonist MRS2578 (50 μmol/L). In addition, P2Y1 receptor antagonist MRS2500 (1 μmol/L) not only abolished α,β-Me-ATP-induced relaxation, but also suppressed 2-Me-S-ADP-induced relaxation. Conclusion: P2Y receptor agonist-induced transient relaxation of rat ileum smooth muscle strips is mediated predominantly by P2Y1 receptor, but also by P2Y6 and P2Y13 receptors, and involves PLC, IP3, Ca2+ release and SK channel activation, but is independent of acetylcholine and NO release.